2017
DOI: 10.1590/1807-3107bor-2017.vol31.0004
|View full text |Cite
|
Sign up to set email alerts
|

One-year aging effects on microtensile bond strengths of composite and repairs with different surface treatments

Abstract: The present study aimed to evaluate effects of different surface treatments and aging of composite cylinders on bond strength of composite resin repair. Thirty-two composite cylinders were produced and divided into four groups according to type of surface treatment and storage time of composite cylinder and repair. Cylinder surface of control group (G control ) received no treatment before composite repair. Other groups were sandblasted with aluminum oxide (G Al2O3 ), followed by silane (G Al2O3sil ) or adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 28 publications
2
26
0
1
Order By: Relevance
“…While some studies were consistent with this result [18], some studies found that the application was satisfactory [21]. As for air abrasion, numerous studies have shown that significantly improves bond strength in the repair of RBC restorations [35][36][37]. However, only 5% of Turkish dentists responded that they use air abrasion in the treatment of repair.…”
Section: Discussionmentioning
confidence: 65%
“…While some studies were consistent with this result [18], some studies found that the application was satisfactory [21]. As for air abrasion, numerous studies have shown that significantly improves bond strength in the repair of RBC restorations [35][36][37]. However, only 5% of Turkish dentists responded that they use air abrasion in the treatment of repair.…”
Section: Discussionmentioning
confidence: 65%
“…In this study, Al 2 O 3 increased the bonding strength significantly in the repair process of the RBCs. Most of the previous studies have also found that Al2O3 increases the bond strength significantly (16,(24)(25)(26)(27)(28)(29)(30)(31)(32), but a few studies found that opposite results (33,34). Al2O3 has the ability to form micro retention areas and these areas increase wettability and adhesion to the restoration (35).…”
Section: Discussionmentioning
confidence: 98%
“…In our study, the thermal cycle process was applied after the bonding with the aim of imitating the oral environment. However, in many studies, it has been shown that the thermocycling procedure reduces the bonding strength by a significant amount (16). Stallings,et al (22) noted that when the coating is not applied, the bonding strength of the Equia system will be reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Isto ocorre devido à ausência de interação química entre a matriz resinosa e as partículas de CaP, o que resulta em uma concentração de tensões na interface matriz/partícula favorecendo a propagação de trincas que levam à fratura do material[15,16]. Assim, a associação entre partículas de reforço e partículas de CaP se faz necessária[9,15,17].Independentemente da presença de partículas de CaP, compósitos resinosos sofrem degradação no ambiente oral, o que se reflete na redução das suas propriedades mecânicas[18][19][20]. A degradação está intimamente ligada à presença de grupos éster nos monômeros constituintes da matriz resinosa, altamente suscetíveis a mecanismos de oxidação e hidrólise quando expostos a fluidos e enzimas salivares[21].…”
unclassified